Respon Orang Tua terhadap Pembelajaran Daring selama Pandemi Covid-19 - Bararathul Adzma; Jelita Jelita; Fenny Anggreni (At-Tafkir, 2022)
In 2020, the learning process underwent a change, from face-to-face learning to BDR (Learning from Home) or known as Online Learning (In Network). This is because, due to a virus outbreak that has hit all countries including Indonesia, the government has issued a policy on WFH (Work from Home), which is a learning system that is carried out from home using mobile phones, the internet and supporting applications. The implementation of online learning, triggers various comments and objections that occur in the field, such as the lack of facilities, infrastructure, learning burden, finance and time. This study aims to determine the response of parents to online learning during Covid-19. This study uses a qualitative descriptive method, namely the research carried out focused on a particular case to be observed and analyzed carefully to completion. In this study, the methods used to analyze the data are data reduction, data presentation and conclusion drawing. The results of the study indicate that the response of parents to online learning when accompanying and guiding children in carrying out learning is in terms of facilities, infrastructure, learning load, financially and time